A case of radiation-induced subclavian artery stenosis treated with percutaneous transluminal angioplasty. Issue 2 (August 2015) - Yamanaka, Tetsuo; Fukatsu, Toru; Satou, Hajime; Ichinohe, Yoshimaro; Komatsu, Hirotaka; Hirata, Yasunobu
Abstract: We report on a female patient who underwent a standard radical mastectomy and radiation therapy for right breast cancer at the age of 50 years without recurrence. At the age of 76 years, she started to experience fatigue in the right upper limb. The symptom gradually worsened and she was admitted to our hospital for further investigation. With computed tomography scan and angiography, we observed a high degree of subclavian artery (SCA) stenosis and asymptomatic right common carotid artery (CCA) stenosis. After undergoing carotid artery stenting to the right CCA stenosis at another hospital, we performed percutaneous transluminal angioplasty to SCA. Although we chose to treat the highly calcified lesion only with a balloon and slightly decreased the degree of stenosis, her symptoms clearly improved. Since arterial severely stenotic lesions were limited in the area of radiation exposure while other part of the arteries looked smooth and relatively free of sclerosis, it was highly suspected that arterial injury was induced by radiation. There are few reports of radiation-induced injury of upper limbs. However, this case suggests that we need to consider the possibility of radiation-induced arterial injury in patients with a history of radiation therapy. <Learning objective: There are few reports regarding upper limb arterial stenosis and occlusion due to radiation-induced arterial injury. However, the underlying mechanism might be overlooked because the symptoms such as fatigue and numbness of the upper limb caused by arterial stenosis and occlusion resembled those of lymphedema and nerve disorders that frequently occur after mastectomy. This case suggests that we need to consider the possibility of radiation-induced arterial injury in the patients with a history of radiation therapy.>